Importance of social capital at the workplace for return to work among women with a history of long-term sick leave: a cohort study - Ingela Rydström; Lotta Dalheim Englund; Lotta Dellve; Linda Ahlstrom (BMC, 2017)
Abstract Background The workplace is an essential source of social capital for many people; it provides mutual support and gives meaning to life. However, few prospective studies have thoroughly investigated the importance of aspects of social capital in the workplace. The aim of this study was to investigate the associations between aspects of social capital (social support, sense of community, and quality of leadership) at the workplace, and work ability, working degree, and vitality among women with a history of long-term sick leave from human service organizations. Methods A longitudinal cohort study was performed among women with a history of long-term sick leave. The study started in 2005, and the women were followed up at 6 months, 1 year, and 6 years using self-reported questionnaires (baseline n = 283). Linear mixed models were used for longitudinal analysis of the repeated measurements of prospective degree of work ability, working degree, and vitality. Analyses were performed with different models; the explanatory variables for each model were social support, sense of community, and quality of leadership and time. Results Social capital in terms of quality of leadership (being good at solving conflicts and giving high priority to job satisfaction), sense of community (co-operation between colleagues) and social support (help and support from immediate superiors and colleagues) increased the women's work ability score (WAS) as well as working degree over time. Additionally, social capital in terms of quality of leadership increased the women's vitality score over time. Conclusions A sustainable return-to-work process among individuals with a history of long-term sick leave, going in and out of work participation, could be supported with social support, good quality of leadership, and a sense of community at the workplace. The responsibility for the rehabilitation process can not be reduced to an individual problem, but ought to include all stakeholders involved in the process, such as managers, colleagues, health care services, and the social security agency.